2020
DOI: 10.1002/ece3.7119
|View full text |Cite
|
Sign up to set email alerts
|

Implications for the mesopelagic microbial gardening hypothesis as determined by experimental fragmentation of Antarctic krill fecal pellets

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…9 ). Copepods have been observed to fragment FP 44 and it was recently shown experimentally that, depending on the FP composition, POC turnover rates can be significantly higher in fragmented compared to non-fragmented FP 45 . On a larger scale, Briggs et al 46 showed that fragmentation of sinking particles may explain 50% of the total carbon flux attenuation in the SO and North Atlantic.…”
Section: Discussionmentioning
confidence: 99%
“…9 ). Copepods have been observed to fragment FP 44 and it was recently shown experimentally that, depending on the FP composition, POC turnover rates can be significantly higher in fragmented compared to non-fragmented FP 45 . On a larger scale, Briggs et al 46 showed that fragmentation of sinking particles may explain 50% of the total carbon flux attenuation in the SO and North Atlantic.…”
Section: Discussionmentioning
confidence: 99%
“…Further DOC may be released from phytoplankton cells via protozoan and zooplankton grazing, such as sloppy feeding, where 12%–50% of intercellular DOC is released into surrounding waters (Møller et al., 2003; Nagata et al., 2000). Antarctic krill release high but variable amounts of DOC (205 ± 77.7 mmol C m −2 d −1 , Ruiz‐Halpern et al., 2011) in their faecal pellets which may be colonized by bacteria following pellet fragmentation (Cavan et al., 2021). Krill may support heterotrophic bacteria and microbial remineralization of both carbon and dFe (Cavan et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The major consequence of sinking particle disaggregation is the enhancement of the development of associated microbial communities by providing more time for detritus into essential compounds conversion (van der Jagt et al 2020). In turn, these non-sinking nutritive materials could be efficiently harvested by zooplankton (Mayor et al 2014;Sanders et al 2016;Cavan et al 2021). Mayor et al (2014) speculate that fragmentation could be a deliberate behavior of zooplankton to promote harvestable production of microbial biomass from poor quality POC, terming this phenomenon "microbial gardening".…”
Section: Disaggregated Sinking Particlesmentioning
confidence: 99%